PEMANFAATAN DAN PENINGKATAN NILAI EKONOMIS LIMBAH PARALON DI DUKUH TEMPEL, CATUR TUNGGAL, DEPOK, SLEMAN - Nurkhamim Nurkhamim; Sri Harjanti (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Many people confront the problem of handling inorganic waste, this is also confronted by the people of Catur Tunggal Village, Depok District, part of Sleman Regency, D.I Province. Yogyakarta. Catur Tunggal Village is known as a village with a leading sector with several well-known campuses as the best educational places in Indonesia such as UGM, UNY, UPN "Veteran" Yogyakarta and others. In addition, there are also many hotels and large malls. This encourages the construction of boarding houses, the construction of hotels, malls, restaurants and the rapidly growing tourism sector. The rapid development has an impact on the environment, one of the impacts that arise is the problem of dealing with construction waste such as paralon waste, wood waste, cement wrapping paper and others. Currently, the waste generated from the construction sector has not been utilized optimally.If paralon waste is managed and utilized properly and processed by skilled hands, it can turn out to be interesting goods and have a high selling value. Opposite, it can also be an exotic work of art. It is enough with simple equipment and cheap additional materials to produce art items such as decorative lamps, bed lamps, wall decorations, sculptures, and so on, so that it is hoped that they can overcome the problem of inorganic waste, increase people's income and reduce unemployment.